Clinical grade allogeneic human mesenchymal stem cells restore alveolar fluid clearance in human lungs rejected for transplantation - McAuley, D. F. (American Physiological Society, 2014)
The lack of suitable donors for all solid-organ transplant programs is exacerbated in lung transplantation by the low utilization of potential donor lungs, due primarily to donor lung injury and dysfunction, including pulmonary edema. The current studies were designed to determine if intravenous clinical-grade human mesenchymal stem (stromal) cells (hMSCs) would be effective in restoring alveolar fluid clearance (AFC) in the human ex vivo lung perfusion model, using lungs that had been deemed unsuitable for transplantation and had been subjected to prolonged ischemic time. The human lungs were perfused with 5% albumin in a balanced electrolyte solution and oxygenated with continuous positive airway pressure. Baseline AFC was measured in the control lobe and if AFC was impaired (defined as <10%/h), the lungs received either hMSC (5 × 10(6) cells) added to the perfusate or perfusion only as a control. AFC was measured in a different lung lobe at 4 h. Intravenous hMSC restored AFC in the injured lungs to a normal level. In contrast, perfusion only did not increase AFC. This positive effect on AFC was reduced by intrabronchial administration of a neutralizing antibody to keratinocyte growth factor (KGF). Thus, intravenous allogeneic hMSCs are effective in restoring the capacity of the alveolar epithelium to remove alveolar fluid at a normal rate, suggesting that this therapy may be effective in enhancing the resolution of pulmonary edema in human lungs deemed clinically unsuitable for transplantation.